LUSH odorant-binding protein mediates chemosensory responses to alcohols in Drosophila melanogaster. - Kim, M.S.; Repp, A.; Smith, D.P. (Genetics, 1998)
The molecular mechanisms mediating chemosensory discrimination in insects are unknown. Using the enhancer trapping approach, we identified a new Drosophila mutant, lush, with odorant-specific defects in olfactory behavior. lush mutant flies are abnormally attracted to high concentrations of ethanol, propanol, and butanol but have normal chemosensory responses to other odorants. We show that wild-type flies have an active olfactory avoidance mechanism to prevent attraction to concentrated alcohol, and this response is defective in lush mutants. This suggests that the defective olfactory behavior associated with the lush mutation may result from a specific defect in chemoavoidance. lush mutants have a 3-kb deletion that produces a null allele of a new member of the invertebrate odorant-binding protein family, LUSH. LUSH is normally expressed exclusively in a subset of trichoid chemosensory sensilla located on the ventral-lateral surface of the third antennal segment. LUSH is secreted from nonneuronal support cells into the sensillum lymph that bathes the olfactory neurons within these sensilla. Reintroduction of a cloned wild-type copy of lush into the mutant background completely restores wild-type olfactory behavior, demonstrating that this odorant-binding protein is required in a subset of sensilla for normal chemosensory behavior to a subset of odorants. These findings provide direct evidence that odorant-binding proteins are required for normal chemosensory behavior in Drosophila and may partially determine the chemical specificity of olfactory neurons in vivo.